Asian Oceanian Radiology Forum 2018: International Education of Radiology in Asian Oceanian Countries - Beck, Kyongmin Sarah (Korean J Radiol, 2020)
According to the reports presented at the Fourth Asian Oceanian Radiology Forum (AORF) 2018, organized by the Korean Society of Radiology during the Korean Congress of Radiology in September 2018 in Seoul, there is an increasing demand for the Asian Oceanian Society of Radiology and its member societies for international education in radiology in the Asian Oceanian region. In AORF 2018, the national delegates of the Asian Oceanian radiological partner societies primarily discussed their societies' activities and current status of international education in radiology.